Identification and validation of biomarkers related to Th1 cell infiltration in neuropathic pain - Xiangsheng Zhang; Jiurong Cheng; Yingdong Deng; Caiyun Guo; Yu Cao; Suo Wang; Chenxi Zhou; Ziqiang Lin; Simin Tang; Jun Zhou (BMC, 2023)
Abstract Neuropathic pain (NP) is a widespread chronic pain with a prevalence of 6.9-10% in the general population, severely affecting patients' physical and mental health. Accumulating evidence indicated that the immune environment is an essential factor causing NP. However, the mechanism is unclear. This study attempted to analyze NP-related immune infiltration patterns. We downloaded the expression profiles from the Gene Expression Omnibus (GEO) database. The novel method of single-sample gene set enrichment analysis (ssGSEA) algorithm and weighted gene co-expression network analysis (WGCNA) was applied to identify immune-related genes and verified in vitro and in vivo experiments. The spared nerve injury (SNI) group was closely related to type1 T helper cells (Th1 cells), and two key genes (Abca1 and Fyb) positively correlated with Th1 cell infiltration. At the single-cell level, Abca1 and Fyb were significantly expressed in macrophages. In addition, we verified that Abca1 could affect the function of macrophages. Finally, we hypothesized that Abca1 is involved in the infiltration of Th1 cells into dorsal root ganglion (DRG) tissues and induces NP via immunoinflammatory response. Hence, the present study aimed to elucidate the correlation between NP and neuroinflammation and identify a new therapeutic target for treating NP.